How are translations created? Using multimodal conversation analysis to study a team translation process - Hirvonen, Maija; Tiittula, Liisa (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2019)
This article demonstrates a methodology for studying the translation process from the perspective of multimodal social interaction and applies this methodology to a case analysis of collaborative audio description. The methodology is multimodal conversation analysis, which aims to uncover the way in which multimodal communication resources (e.g., talk, gaze, gestures) are used holistically and situatedly in building human action. Being empirical and data-driven, multimodal conversation analysis observes human conduct in its natural setting. This article analyses video data from an authentic audio-description process and presents the multimodal constitution of problem-solving sequences during translating. In addition, the article discusses issues regarding the methodological choices facing researchers who are interested in human interaction in translation. The article shows that applying multimodal conversation analysis opens new avenues for research into the translation process and collaborative translation.